KEPEMIMPINAN INTRUKSIONAL KEPALA MADRASAH DALAM INOVASI KURIKULUM DI MADRASAH TSANAWIYAH SWASTA DAYAH DARUL IHSAN ACEH BESAR - Sinaga, M Fadly Syahputra; Fitri, Hazal; Marsithah, Iis; Safriadi, Safriadi (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the form of instructional leadership of the madrasah principal and the efforts made in encouraging curriculum innovation at the Private Islamic Junior High School Dayah Darul Ihsan Aceh Besar. The method used is a qualitative approach with a descriptive type. The research subjects included the madrasah principal as the main informant, as well as the deputy head of curriculum and teachers as supporting informants. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion, with validity tests through triangulation and member checking. The results of the study indicate that the instructional leadership of the madrasah principal is participatory and transformational and oriented towards improving the quality of learning. The madrasah principal plays an active role in the planning, implementation, and evaluation of learning and is able to integrate the national curriculum with Islamic boarding school values. Efforts made include academic supervision, strengthening a collaborative culture, and teacher professional development through training and sharing of good practices that have an impact on improving the quality of learning, the application of innovative methods, and the involvement and critical thinking skills of students.